2011
DOI: 10.1111/j.1755-263x.2011.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat re-creation strategies for promoting adaptation of species to climate change

Abstract: Creation of new habitat could help species respond to climate change by facilitating range expansion in fragmented landscapes. However, there are currently no guidelines for deciding where new habitat should be placed to promote range changes. We developed a model to simulate the expansion of populations across a heavily fragmented landscape in the United Kingdom, and investigated the effectiveness of six habitat creation strategies for woodland, grassland, heathland, and wetland habitats. A strategy aimed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 38 publications
2
76
0
Order By: Relevance
“…With careful design though (see Optimal scenario), additional habitat in multifunctional landscapes can indeed strengthen ecological networks, incorporating requirements for both the spatial conditions, habitat density and connectivity, and abiotic conditions (locations with high ground water levels).While it can be expected that different adaptation strategies are optimal for either the facilitation of range shifts, or the facilitation of species viability (e.g. Hodgson et al 2011), our findings are in line with Hodgson et al (2012), who found that when habitat has a channelled pattern (as in scenario Optimal, this study), it is possible to achieve both rapid advance and relatively high patch occupancy, for a large array of species.…”
Section: Discussionmentioning
confidence: 99%
“…With careful design though (see Optimal scenario), additional habitat in multifunctional landscapes can indeed strengthen ecological networks, incorporating requirements for both the spatial conditions, habitat density and connectivity, and abiotic conditions (locations with high ground water levels).While it can be expected that different adaptation strategies are optimal for either the facilitation of range shifts, or the facilitation of species viability (e.g. Hodgson et al 2011), our findings are in line with Hodgson et al (2012), who found that when habitat has a channelled pattern (as in scenario Optimal, this study), it is possible to achieve both rapid advance and relatively high patch occupancy, for a large array of species.…”
Section: Discussionmentioning
confidence: 99%
“…Hodgson et al (2011b), on the other hand, found that their "random" (new habitat added to cells chosen at random) and "even" (new habitat added to cells with lowest connectivity) strategies gave the most consistent increases in range expansion speed, and that "aggregation" was the least effective at facilitating range expansion. Whilst these findings are in stark contrast to…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The modelling framework presented here, in contrast to many studies (although note: (Hodgson et al, 2011b)), is applied to a real landscape and aims to represent climate change adaptation strategies at achievable scales (both in terms of total area prescribed for adaptation action and the size distribution of individual actions). Multiple species are separately modelled, with realistic traits and the incorporation of population dynamics and dispersal behaviour, but without considering biotic interactions.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The main appeal for larger sites within modern-day landscape-scale conservation, however, is the capacity to enhance range shift. Large source populations in reserves enhance colonization of surrounding habitat, supporting metapopulation persistence in highly fragmented landscapes (Wilson et al 2002;Lawson et al 2012), thus facilitate range shifts in the face of climate change (Hodgson et al 2011b). Moreover, large sites have been advocated for their ability to support greater species richness (e.g.…”
Section: Space For Naturementioning
confidence: 99%